(x+8)(3x-4)=0

Simple and best practice solution for (x+8)(3x-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+8)(3x-4)=0 equation:


Simplifying
(x + 8)(3x + -4) = 0

Reorder the terms:
(8 + x)(3x + -4) = 0

Reorder the terms:
(8 + x)(-4 + 3x) = 0

Multiply (8 + x) * (-4 + 3x)
(8(-4 + 3x) + x(-4 + 3x)) = 0
((-4 * 8 + 3x * 8) + x(-4 + 3x)) = 0
((-32 + 24x) + x(-4 + 3x)) = 0
(-32 + 24x + (-4 * x + 3x * x)) = 0
(-32 + 24x + (-4x + 3x2)) = 0

Combine like terms: 24x + -4x = 20x
(-32 + 20x + 3x2) = 0

Solving
-32 + 20x + 3x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-8 + -1x)(4 + -3x) = 0

Subproblem 1

Set the factor '(-8 + -1x)' equal to zero and attempt to solve: Simplifying -8 + -1x = 0 Solving -8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -1x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -1x = 0 + 8 -1x = 0 + 8 Combine like terms: 0 + 8 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8

Subproblem 2

Set the factor '(4 + -3x)' equal to zero and attempt to solve: Simplifying 4 + -3x = 0 Solving 4 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3x = 0 + -4 -3x = 0 + -4 Combine like terms: 0 + -4 = -4 -3x = -4 Divide each side by '-3'. x = 1.333333333 Simplifying x = 1.333333333

Solution

x = {-8, 1.333333333}

See similar equations:

| 16x^2+60x-100=0 | | 8y+2=166.8 | | 0=15x^2-92x+12 | | 1/9=w/w+24 | | 0.3x+0.7=3x | | 3k-2=18 | | x-2y+13= | | 0.3+0.7=3x | | 4x+3y-2=-14 | | -2x+19=3k-1 | | x+12=2x-40 | | 5/7=3w/21 | | x+(x+4)=300 | | 2(2x-9)=1/2(8x-32) | | 4x-42=x | | 22+70=17x-95 | | (3y+2)(y+2)=-3(y+2) | | 3xy=8 | | 3x^2-12x-4=y | | 8y^4(y^2-7y)+4y^6=0 | | 6x+3(-2x-7)=-19-2x | | (x-4)(x+8)=2(x-12) | | 4y^2+11y=-6 | | 3x+15=5(3x-3) | | 5(n+2)=(5+10n) | | 3*7x=-9 | | 6p+6=5p+8 | | 64s^2-48s+9= | | 0.5-3d+5=0 | | 3*x-15=12 | | 7x-8=4x+7 | | -4(y+4)-(-3y-5)=-7 |

Equations solver categories